Comparison of Immunological Characteristics of Mesenchymal Stem Cells Derived from Human Embryonic Stem Cells and Bone Marrow - Fu, Xin (Tissue Eng Part A, 2015)
Mesenchymal stem cell (MSC) has great potential for both regenerative medicine and immunotherapy due to its multipotency and immunomodulatory property. The derivation of MSCs from human tissues involves an invasive procedure and the obtained MSCs often suffer from inconsistent quality. To overcome these issues, the approaches of deriving a highly potent and replenishable population of MSCs from human embryonic stem cells (hESCs) were established. However, few studies compared the immunological characteristics of MSCs derived from hESCs with tissue-derived MSCs or demonstrated differences and the underlying mechanisms. Here, we differentiated H9 hESCs into MSC-like cells (H9-MSCs) through an embryoid body outgrowth method and compared the immunological characteristics of H9-MSCs with bone marrow-derived MSCs (BMSCs). Both sources of derived cells exhibited typical MSC morphologies and surface marker expressions, as well as multipotency to differentiate into osteogenic and adipogenic lineages. A immunological characterization study showed that H9-MSCs and BMSCs had similar immunoprivileged properties without triggering allogeneic lymphocyte proliferation as well as equivalent immunosuppressive effects on T-cell proliferation induced by either cellular or mitogenic stimuli. Flow cytometry analysis revealed a lower expression of human major histocompatability complex class II molecule human lymphocyte antigen (HLA)-DR and a higher expression of coinhibitory molecule B7-H1 in H9-MSCs than in BMSCs. Interferon gamma (IFN-γ) is a proinflammatory cytokine that can induce the expression of HLA class II molecules in many cell types. Our results showed that pretreatment of H9-MSCs and BMSCs with IFN-γ did not change their immunogenicity and immunosuppressive abilities, but increased the difference between H9-MSCs and BMSCs for their expression of HLA-DR. Further detection of expression of molecules involved in IFN-γ signaling pathways suggested that the lower expression of HLA-DR in H9-MSCs could be partially attributed to the lower expression and the less nuclear translocation of its transcriptional factor CIITA. The present study provides evidence that the hESC-derived MSCs share similar immunogenicity and immunosuppressive abilities with BMSCs, but differ in the expression profile of immunological markers and the responsiveness to certain inflammatory cytokines, which suggests that H9-MSCs could be a safe and efficient candidate for MSC treatment in patients with inflammatory disorders.